AgriTech4Uzbekistan Innovation Challenge: Demo Day - CGIAR Accelerate for Impact Platform (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The AgriTech4Uzbekistan Innovation Challenge is powered by the CGIAR Accelerate for Impact Platform and co-designed with CGIAR centers ICARDA, IWMI, and the Alliance of Bioversity International and CIAT. The project is implemented in collaboration with Hackonnect, IT Park, innoWIUT Entrepreneur’s Lab of Westminster International University in Tashkent, the United Nations Development Programme Uzbekistan, FAO, the Agency of Innovative Development under the Ministry of Higher Education, Science and Innovation of Uzbekistan, the Ministry of Agriculture of Uzbekistan through the AKIS Center, Indorama, the Uzbekistan Venture Capital Association, the Tashkent State Agrarian University, and the International Agriculture University.